Blockchain Technology For Circular Economy In Plastic Bank - Priyana, I Putu Okta; Utami, Made Ayu Jayanti Prita; Saputra, Upayana Wiguna Eka (Politeknik Ganesha Medan, 2023)
With the use of blockchain technology, this research sought to understand the applications, benefits, and limitations faced by circular economy-based businesses. This research was conducted at the Plastic Bank Company, which used a digital conference room to allow interviews that could not be conducted in person, as well as the researcher's residence for online data gathering and document review. Five management members of the Plastic Bank Company comprise the sample population. The information used is first-hand information derived from interview findings. In order to acquire data, several methods including interviews, document analysis, and observation were applied and tested by Triangulation. The findings of this study revealed: 1) Companies with a circular economy may employ blockchain technology to change supply chain operations, tracking, and tracing. 2) Blockchain technology has benefits for businesses based on the circular economy, including easier distribution management, less duplicate papers, increased cost effectiveness, and the ability to turn plastic trash into digital cash. 3) The general public is still unaware of the use of blockchain technology for businesses that rely on the circular economy. Furthermore, the company's success is constrained on a small scale due to the absence of finance from affiliated parties. Therefore, in order to grow the use of technology on a big scale, this circular-based economy firm for plastic banks has to strengthen its performance and efforts.